Preparation method of isobutene ammoxidation catalyst and application thereof

CN118059880BActive Publication Date: 2026-10-23XIAMEN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410345816.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2026-10-23
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

CN101970109A中异丁烯转化率77.15%,甲基丙烯腈单程转化率为51.7%,较难在工业上得到实际应用

Benefits of technology

[0024]1、本发明采用具有高比表面(比表面积>100m2/g)的白炭黑作为初级载体,通过浸渍法负载金属氧化物增强氧化功能组分在催化剂中的分散程度,从而提高甲基丙烯腈的选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118059880B_ABST
    Figure CN118059880B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an isobutylene ammoxidation catalyst and application thereof, and comprises the following steps: (1) stirring uniformly ammonium molybdate and ammonia water in deionized water to obtain solution A; (2) dissolving bismuth nitrate, iron nitrate, magnesium nitrate, nickel nitrate and potassium nitrate and citric acid in deionized water to obtain solution B; (3) dropping solution B into solution A under the condition of a water bath at 70-90 DEG C, and then adding citric acid to stir to obtain a complex complex solution C; (4) adding white carbon black powder with a specific surface area greater than 100 m 2 / g into the above complex complex solution C, fully stirring, and then standing at room temperature for 10-12 h; then adding polyvinyl alcohol and continuously stirring at 50-60 DEG C to form a stable suspension emulsion; then sequentially drying and calcining to obtain a composite powder; (5) mixing and beating silicon sol, cordierite micro powder, carboxymethyl cellulose and a small amount of water, then adding the composite powder obtained in the step (4), and then mixing and kneading into a plastic material, and then sequentially drying and calcining to obtain the isobutylene ammoxidation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of producing unsaturated nitrile compounds from low-carbon olefins, specifically relating to a method for preparing an isobutylene ammoxidation catalyst and its application. Background Technology

[0002] Acrylonitrile, methacrylonitrile, and other unsaturated nitriles are important chemical products. The cyano group on nitrile is highly reactive, readily undergoing oxidation, hydrolysis, hydrogenation, and polymerization reactions, and is widely used as an intermediate in the synthesis of chemical materials. Methacrylonitrile, through esterification and hydrolysis, produces methacrylates, which are important monomers for polymers, crucial raw materials for acrylic glass and other synthetic resins, and can also be homopolymerized or copolymerized with other monomers to produce plastics or fibers. Acrylonitrile was first synthesized by the French scientist Moureu in the late 19th century, and industrial production was truly achieved in the 1940s. In the 1980s, Asahi Kasei Corporation of Japan successfully developed a method for synthesizing methacrylonitrile from tert-butanol via dehydration and ammoxidation, and achieved the first industrial-scale production.

[0003] Currently, the production of unsaturated nitriles from low-carbon olefins typically employs a multi-component composite catalyst composed of Mo-Bi-Fe-O composite oxides and an acidic support, SiO2. The technical solution disclosed in US3326422A uses an iron, bismuth, molybdenum, and phosphorus composite oxide for the ammoxidation of propylene to acrylonitrile. In the Mo-Bi-Fe catalytic system, transition elements such as Ce and Mn are added to improve the fluidity of lattice oxygen in the catalyst, and alkali metals and alkaline earth metals are added to adjust the acidity and basicity of the catalyst. Furthermore, the introduction of Co, Ni, and Mg can form solid solutions with the active components to improve the stability of the redox cycle during the catalyst reaction. Patent CN1053197A discloses a mixed ammoxidation catalyst for propylene and isobutylene, wherein the catalyst contains oxides of bismuth, molybdenum, iron, nickel, and magnesium, at least one element selected from potassium and cesium, and may also contain one element selected from cobalt, phosphorus, manganese, tellurium, sodium, cerium, chromium, antimony, and tungsten. However, the composition and preparation process are complex, and the product selectivity is not high. CN112121811A discloses a catalyst for the ammoxidation of isobutylene to methacrylonitrile prepared by adding elements such as Ni, Mg, K, Ba, and Cu to a Mo-Bi-Fe system and using a co-precipitation method. The catalyst achieves a maximum isobutylene conversion of 93.64% and a methacrylonitrile selectivity of 86.11%. In addition, vanadium-antimony-niobium catalyst systems have also been developed. CN101970109A presents an isobutylene conversion of 77.15% and a single-pass methacrylonitrile conversion of 51.7%, which is difficult to apply industrially.

[0004] Although propylene ammoxidation catalysts have been widely used, isobutylene is more reactive and has a greater impact on product selectivity. Therefore, existing industrial propylene ammoxidation catalysts cannot be applied to isobutylene ammoxidation. Currently developed Mo-Bi-Fe system isobutylene ammoxidation catalysts mainly employ silica sol, using co-precipitation or impregnation methods. Existing Mo-based catalysts suffer from drawbacks such as complex composition, low selectivity for the target product, and a large number of byproducts. Ammoxidation is a highly exothermic reaction, which is prone to overheating, leading to deactivation and reduced selectivity. Improving the selectivity for the target product is a key issue. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects of the prior art and provide a method for preparing an isobutylene ammonia oxidation catalyst.

[0006] Another object of the present invention is to provide the application of the isobutylene ammoxidation catalyst prepared by the above preparation method.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing an isobutylene ammoxidation catalyst includes the following steps:

[0009] (1) Dissolve ammonium molybdate and ammonia in deionized water and stir until homogeneous to obtain solution A;

[0010] (2) Dissolve bismuth nitrate, ferric nitrate, magnesium nitrate, nickel nitrate, potassium nitrate, and citric acid in deionized water to obtain solution B;

[0011] (3) Add solution B dropwise to solution A under a water bath at 70-90℃, and then add citric acid and stir to obtain a complex solution C;

[0012] (4) For surfaces with a specific surface area > 100m² 2 / g of silica powder was added to the above-mentioned composite complex solution C and stirred thoroughly. The solution was then allowed to stand at room temperature for 10-12 hours. Polyvinyl alcohol was then added and stirred at 50-60℃ to form a stable suspension emulsion. The solution was then dried and calcined sequentially to obtain the composite powder. The chemical formula of this composite powder is K. a Mg b Ni c Mo d Bi e Fe f O x / SiO2, a=0-1, b=0-2.5, c=4-6, d=10-13, e=0.5-1, f=1.5-3, x is the total number of oxygen atoms required to satisfy the valence;

[0013] (5) Mix silica sol, cordierite powder with a particle size of <100um, carboxymethyl cellulose and a small amount of water to form a slurry, then add the composite powder obtained in step (4), knead it into a plastic mass, and then dry and calcine it to obtain the isobutylene ammonia oxidation catalyst.

[0014] In a preferred embodiment of the present invention, the amount of polyvinyl alcohol added is 2-3 wt% of the silica powder.

[0015] In a preferred embodiment of the present invention, the drying temperature in steps (4) and (5) is 100-120°C.

[0016] In a preferred embodiment of the present invention, the calcination in step (4) specifically involves heating to 600-650°C for 3-5 hours in an air atmosphere at a rate of 5-10°C / h.

[0017] In a preferred embodiment of the present invention, the calcination in step (5) specifically involves calcining at 450-500°C for 3-5 hours in an air atmosphere at a rate of 5-10°C / h.

[0018] In a preferred embodiment of the present invention, in step (5), the total amount of SiO2 and cordierite powder added to the silica sol accounts for 20-30 wt% of the isobutylene ammonia oxidation catalyst, the mass ratio of SiO2 and cordierite powder in the silica sol is 1:1, and the amount of carboxymethyl cellulose added is 2-3 wt% of the isobutylene ammonia oxidation catalyst.

[0019] The use of the isobutylene ammoxidation catalyst prepared by the above method in the preparation of methacrylonitrile.

[0020] A method for preparing methacrylonitrile by ammoxidation of isobutylene, using the isobutylene ammoxidation catalyst prepared by the above method as the catalyst.

[0021] In a preferred embodiment of the present invention, the reaction is carried out in a fixed-bed reactor or a tubular reactor at atmospheric pressure and at a temperature of 380-430°C. The feed volume ratio is isobutylene:ammonia:air:water = 1:1.2-1.5:9-10:2-4.

[0022] More preferably, the isobutylene ammoxidation catalyst is activated as follows: the temperature is increased to 350°C in air at a rate of 3-5°C / h, ammonia gas is introduced for ammonia combustion treatment for 3-5 hours, the catalyst bed is stabilized at 350-370°C, and the air space velocity is 2000-3000 h⁻¹. - The air / ammonia gas volume ratio is 10:1.0-1.2; nitrogen purging is performed after activation.

[0023] The beneficial effects of this invention are:

[0024] 1. This invention utilizes materials with a high specific surface area (specific surface area > 100 m²). 2 Using precipitated silica (g) as a primary support, metal oxides are loaded via impregnation to enhance the dispersion of oxidizing functional components in the catalyst, thereby improving the selectivity of methacrylonitrile.

[0025] 2. This invention uses cordierite micro powder, which has good thermal conductivity and thermal stability, as an inert structural additive and isolating agent, which can effectively prevent excessive oxidation and oxide crystal phase sintering caused by local overheating, and improve the stability of the catalyst.

[0026] 3. The ammonia oxidation reaction of the present invention mainly follows the redox reaction mechanism of Mo, and the mobility of lattice oxygen has a significant impact on the performance of the catalyst. Attached Figure Description

[0027] Figure 1 The images show the H2-TPR spectra of the catalysts after activation treatment in Examples 1, 5, 6, and 7 of this invention.

[0028] Figure 2 The figure shows the experimental results of the stability of the catalyst of this invention. Detailed Implementation

[0029] The technical solution of the present invention will be further explained and described below with reference to specific embodiments and accompanying drawings.

[0030] Example 1

[0031] (1) Dissolve 211.862g of ammonium molybdate and 100ml of ammonia in deionized water and stir to obtain a homogeneous solution A;

[0032] (2) Dissolve 24.254g bismuth nitrate, 80.799g ferric nitrate, 38.460g magnesium nitrate, 145.395g nickel nitrate, 8.088g potassium nitrate, and 20.0g citric acid in deionized water to obtain a homogeneous solution B;

[0033] (3) Add solution B dropwise to solution A under (80)℃ water bath conditions, add an appropriate amount of citric acid and stir until a homogeneous complex solution is obtained.

[0034] (4) Take 150.0g of silica powder (specific surface area of ​​113.5m²) 2 / g) was added to the above composite complex solution C and stirred for 30 min. After standing at room temperature for 10-12 h, 3.0 g of polyvinyl alcohol was added and stirred in a water bath at 50-60 ℃ to form a stable suspension emulsion. Then, it was dried at 100-120 ℃ and calcined at 620 ℃ in air atmosphere for 4 h h at a temperature of 5-10 ℃ / h to obtain the composite powder.

[0035] (5) Add 250.0g of silica sol (SiO2 content of 30%) and 75.0g of cordierite powder to a mixing mill, add 15.0g of carboxymethyl cellulose and a small amount of water to make a slurry. Then add the composite powder obtained in step (4), and knead the plastic lumps into a mixture. Dry the mixture at 100-120℃, and calcine it at 450℃ in air atmosphere for 4 hours at a temperature of 5-10℃ / h to obtain a shaped catalyst, labeled K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite (H2-TPR spectrum as shown) Figure 1 (As shown).

[0036] The catalyst evaluation method in this embodiment is as follows: 10g of the above-mentioned shaped catalyst is loaded into a fixed-bed reactor and activated at atmospheric pressure. The activation process is as follows: the temperature is increased to 350℃ in an air atmosphere at a rate of 3-5℃ / h, and then ammonia gas is introduced for ammonia combustion treatment for 1h. The catalyst bed is stabilized at 350-370℃, and the air space velocity is 2000-3000 h⁻¹. - The air / ammonia gas volume ratio was 10:1.0-1.2. After activation, nitrogen was used for purging, and then the process moved to activity evaluation. The reaction conditions were: isobutylene space velocity of 0.08 h⁻¹. -1 The reaction mixture was prepared with isobutylene:ammonia:air:water in a volume ratio of 1:1.5:10:3, at a temperature of 410℃, for a total reaction time of 8 hours. The tail gas was first treated with a mixed absorbent of ethylbenzene and water to absorb formonitrile, acetonitrile, acrylonitrile, methacrylonitrile, and methacrolein. The collected liquid products were analyzed by gas chromatography-fingerprint analysis (FID) to obtain the selectivity of different liquid products. The inert tail gas was analyzed by transilluminator (TCD) to determine the content of gaseous products (CO + CO2) and unreacted isobutylene, thereby calculating the conversion rate and the selectivity of the gaseous products.

[0037] like Figure 2 As shown, the K obtained in this embodiment 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 The 200-hour stability test results of Fe2Ox / SiO2-cordierite showed that its conversion rate remained basically at 98%.

[0038] Example 2

[0039] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of MgO is changed from 1.5 to 0.5. All other steps and conditions remain unchanged to obtain the catalyst in this example, denoted as K. 0.8 Mg 0.5 Ni5Mo 12 Bi 0.5Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0040] Example 3

[0041] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of MgO is changed to 0. All other steps and conditions remain unchanged to obtain the catalyst in this example, denoted as K. 0.8 Mg0Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0042] Example 4

[0043] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of K₂O is changed from 0.8 to 1.0 and the molar amount of MgO is changed from 1.5 to 1.0. All other steps and conditions remain unchanged to obtain the catalyst in this example, denoted as K. 1.0 Mg 1.0 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0044] Example 5

[0045] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of K₂O is changed from 0.8 to 0.2 and the molar amount of MgO is changed from 1.5 to 1.0. All other steps and conditions remain unchanged to obtain the catalyst in this example, denoted as K. 0.2 Mg 1.0 Ni s Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0046] Example 6

[0047] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of K₂O is changed from 0.8 to 0.2 and the molar amount of MgO is changed from 1.5 to 2.5. All other steps and conditions remain unchanged to obtain the catalyst in this example, denoted as K. 0.2 Mg 2.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0048] Example 7

[0049] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of K₂O is changed from 0.8 to 0 and the molar amount of MgO is changed from 1.5 to 0. All other steps and conditions remain unchanged to obtain the catalyst in this example, labeled as K₀Mg₀Ni₅Mo. 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0050] Example 8

[0051] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of K₂O is changed from 0.8 to 1.2 and the molar amount of MgO is changed from 1.5 to 0. All other steps and conditions remain unchanged to obtain the catalyst in this example, denoted as K. 1.2 Mg0Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0052] Example 9

[0053] The method for preparing the catalyst is similar to that in Example 1, except that the molar amount of K₂O is changed from 0.8 to 0 and the molar amount of MgO is changed from 1.5 to 2.5. All other steps and conditions remain unchanged to obtain the catalyst in this example, labeled as K₀Mg. 2.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite. The activation and evaluation methods for the catalyst are the same as in Example 1.

[0054] Comparative Example 1:

[0055] The catalyst evaluation method is the same as in Example 1. The catalyst preparation method is similar to that in Example 1, except that cordierite powder is replaced with γ-Al₂O₃ powder, and the catalyst is labeled as K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-Al2O3.

[0056] Comparative Example 2:

[0057] The catalyst evaluation method is as described in Example 1. The catalyst preparation process is similar to that in Example 1, except that the cordierite powder is replaced with AlN powder, and the catalyst is labeled as K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-AlN.

[0058] Comparative Example 3:

[0059] The catalyst evaluation method is as described in Example 1. The catalyst preparation process is similar to that in Example 1, except that cordierite powder is replaced with ZrO2 powder, and the catalyst is labeled as K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-ZrO2.

[0060] Comparative Example 4:

[0061] The catalyst evaluation method is as described in Example 1. The catalyst preparation process is similar to that in Example 1, except that SiO2 is replaced with Al2O3 powder and aluminum sol, and the catalyst is labeled as K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / Al2O3.

[0062] Comparative Example 5:

[0063] The catalyst preparation and evaluation methods are similar to those in Example 1, and the catalyst is K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite (H2-TPR spectrum as shown) Figure 1 (As shown). The catalyst activation process was simply modified to: heating to 410℃ in a N2 atmosphere at a rate of 3-5℃ / h, with an N2 gas space velocity of 2000-3000 h⁻¹. - After activation, the activity evaluation process begins.

[0064] like Figure 2 As shown, the K obtained in this comparative example 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 The 200-hour stability test results of Fe2Ox / SiO2-cordierite showed that its conversion rate decreased from 87% to 65%.

[0065] Comparative Example 6:

[0066] The catalyst preparation and evaluation methods are similar to those in Example 1, and the catalyst is K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite (H2-TPR spectrum as shown) Figure 1 (As shown). The catalyst activation process was simply modified as follows: the temperature was increased to 350℃ under a N2 atmosphere at a rate of 3-5℃ / h, followed by ammonia gas treatment for 1 hour, stabilizing the catalyst bed at 350-370℃, with an air space velocity of 2000-3000 h⁻¹.- The volume ratio of N2 gas to ammonia gas was 10:1.0-1.2. After activation, nitrogen was used for purging, and the temperature was programmed to rise to 410℃ before proceeding to the activity evaluation stage.

[0067] Comparative Example 7:

[0068] The catalyst preparation and evaluation methods are similar to those in Example 1, and the catalyst is K. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 Fe2Ox / SiO2-cordierite (H2-TPR spectrum as shown) Figure 1 (As shown). The catalyst activation process was simply modified to: heating to 410℃ in air at a rate of 3-5℃ / h, with an air space velocity of 2000-3000 h⁻¹. - After activation, nitrogen gas is used for purging, and then the activity evaluation begins.

[0069] Table 1. Catalyst activity evaluation results for each example and comparative example.

[0070]

[0071]

[0072] In summary, under fixed-bed conditions and atmospheric pressure, the space velocity of isobutene is 0.08 h⁻¹. -1 The reaction was carried out at a molar ratio of isobutylene:NH3:AIR of 1:1.5:10:3 and a reaction temperature of 410℃. 0.8 Mg 1.5 Ni5Mo 12 Bi 0.5 The Fe2Ox / SiO2-cordierite catalyst exhibited optimal reactivity after air heating / ammonia treatment, achieving a conversion rate of 97.3% for isobutylene and a selectivity of 88.9% for methacrylonitrile.

[0073] In addition, H2-TPR spectroscopic analysis was performed on the catalysts of Example 1, Comparative Examples 5, 6, and 7 after activation treatment, and the results are as follows: Figure 1 As shown, the hydrogen consumption peak of molybdenum oxide appears in the 350-600℃ temperature range. Specifically, after air heating / ammonia treatment, the catalyst significantly shifted from 546℃ to 541℃, overlapping with the low-temperature peak of 416℃. This indicates that air heating / air + ammonia treatment facilitates the removal of lattice oxygen from the molybdenum oxide catalyst, thus enhancing its mobility. In contrast, pure ammonia treatment causes partial destruction of acidic sites in the catalyst, resulting in reduced catalyst activity.

[0074] The above description is merely a preferred embodiment of the present invention, and therefore should not be construed as limiting the scope of the present invention. All equivalent changes and modifications made in accordance with the scope of the patent and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing an isobutylene ammoxidation catalyst, characterized in that: Includes the following steps: (1) Dissolve ammonium molybdate and ammonia in deionized water and stir until homogeneous to obtain solution A; (2) Dissolve bismuth nitrate, ferric nitrate, magnesium nitrate, nickel nitrate, potassium nitrate, and citric acid in deionized water to obtain solution B; (3) Add solution B dropwise to solution A under a water bath at 70-90℃, and then add citric acid and stir to obtain a complex solution C; (4) For surfaces with a specific surface area > 100m² 2 / g of silica powder was added to the above-mentioned composite complex solution C and stirred thoroughly. The solution was then allowed to stand at room temperature for 10-12 hours. Polyvinyl alcohol was then added and stirred at 50-60℃ to form a stable suspension emulsion. The solution was then dried and calcined sequentially to obtain the composite powder. The chemical formula of this composite powder is K. a Mg b Ni c Mo d Bi e Fe f O x / SiO2, a=0-1, b=0-2.5, c=4-6, d=10-13, e=0.5-1, f=1.5-3, x is the total number of oxygen atoms required to satisfy the valence; (5) Mix silica sol, cordierite powder with a particle size of <100um, carboxymethyl cellulose and a small amount of water to form a slurry, and then add the composite powder obtained in step (4). After kneading into a plastic mass, the mass is dried and calcined to obtain the isobutylene ammonia oxidation catalyst. In this step, the total amount of SiO2 and cordierite powder added in the silica sol accounts for 20-30wt% of the isobutylene ammonia oxidation catalyst. The mass ratio of SiO2 and cordierite powder in the silica sol is 1:1, and the amount of carboxymethyl cellulose added is 2-3wt% of the isobutylene ammonia oxidation catalyst.

2. The preparation method according to claim 1, characterized in that: The amount of polyvinyl alcohol added is 2-3 wt% of the precipitated silica powder.

3. The preparation method according to claim 1, characterized in that: In steps (4) and (5), the drying temperature is 100-120℃.

4. The preparation method according to claim 1, characterized in that: The calcination in step (4) specifically involves heating to 600-650 ℃ for 3-5 h in an air atmosphere at a rate of 5-10℃ / h.

5. The preparation method according to claim 1, characterized in that: The calcination in step (5) specifically involves heating to 450-500 ℃ and calcining for 3-5 h at a rate of 5-10℃ / h in an air atmosphere.

6. Use of the isobutylene ammoxidation catalyst prepared by the method according to any one of claims 1 to 5 in the preparation of methacrylonitrile.

7. A method for preparing methacrylonitrile by ammoxidation of isobutylene, characterized in that: The isobutylene ammoxidation catalyst prepared by the preparation method described in any one of claims 1 to 5 is used as the catalyst.

8. The method as described in claim 7, characterized in that: The reaction is carried out in a fixed-bed reactor or a tubular reactor at atmospheric pressure and a temperature of 380-430℃. The feed volume ratio is isobutylene:ammonia:air:water = 1:1.2-1.5:9-10:2-4.

9. The method as described in claim 8, characterized in that: The isobutylene ammoxidation catalyst was activated as follows: the temperature was increased to 350°C in air at a rate of 3-5°C / h, ammonia gas was introduced for ammonia combustion treatment for 3-5 h, the catalyst bed was stabilized at 350-370°C, and the air space velocity was 2000-3000 h⁻¹. -1 The air / ammonia volume ratio is 10:1.0-1.2; nitrogen is used for purging after activation.

Citation Information

Patent Citations

  • Method of making mixed metal oxide catalysts for ammoxidation and / or oxidation of lower alkane hydrocarbons

    CN101970109A

  • Process for manufacture of acrylonitrile and methacrylonitrile

    CN1053197A

  • Catalyst for preparing methacrylonitrile and method of preparing methacrylonitrile

    CN112121811A

  • Seed metering mechanism

    US3326422A

  • Catalyst for manufacturing nitrile and manufacturing method for nitrile

    JP2002035588A